2013
DOI: 10.1111/cen.12122
|View full text |Cite
|
Sign up to set email alerts
|

Role of pituitary dysfunction on cardiovascular risk in primary empty sella patients

Abstract: Primary empty sella patients show increased cardiovascular risk, regardless of BMI. A worse lipid and glucose profile and higher FS were associated with secondary hypothyroidism, even subclinical, as well as hypogonadism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Gonadotropin deficiency was predominantly pituitary hormone deficiency, consistent with previous study [3]. However, GH deficiency was most frequent in pituitary hormone deficiency [4,6,7,11,13,16,19,28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Gonadotropin deficiency was predominantly pituitary hormone deficiency, consistent with previous study [3]. However, GH deficiency was most frequent in pituitary hormone deficiency [4,6,7,11,13,16,19,28].…”
Section: Discussionsupporting
confidence: 90%
“…The common causes of PI are pituitary adenoma and peripituitary tumors [1][2][3]. Other causes include pituitary apoplexy, postpartum pituitary necrosis [Sheehan's syndrome (SS)], empty sella, stroke, traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), and lymphocytic hypopituitarism [1][2][3][4][5][6][7][8][9]. Primary empty sella (PES) is defined as the thinning of the pituitary gland after subarachnoid space herniated into the sella turcica in patients with no history of pituitary tumor, radiotherapy, and surgery [4][5][6]10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypopituitarism, and in particular GHD are associated with several metabolic alterations and cardiovascular risk [6][7][8]17,[23][24][25][26].This brief report showed that also in hypopituitarism due to TBI metabolic impairment is frequent, in particular altered glucose levels, insulin resistance and dyslipidemia, independently by BMI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, interaction with untreated hypogonadism cannot be ruled out because only 2 patients received appropriate replacement therapy. Conversely, hypothyroidism and hypocortisolism were under treatment in all patients when metabolic evaluations were performed, although a role of these deficits has been reported in hypopituitarism due to primary empty sella [26].…”
Section: Discussionmentioning
confidence: 99%